2021
DOI: 10.5455/medarh.2021.75.274-279
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopic Evaluation of Lower Gastrointestinal Bleeding (LGIB): Practical Approach

Abstract: Background: Haematochesia (Lower Gastrointestinal Bleeding (LGIB) is the most common reason for endoscopic examination. Generaly it is caused by hemorrhoids and diverticular disease, but other anorectal conditions can also lead to LGIB. Recurrent bleeding may result in secondary iron deficiency anemia. Colonoscopy is the primary diagnostic option for establishing a diagnosis of colonic bleeding. Objective: This study aimed to analyze symptoms and endoscopic finding (spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Previously, a reduction in the amount of connective tissue collagen was shown in HD. Other authors have reported a decrease in the ratio of type I to III collagen leading to the impaired mechanical stability of the perivascular tissue in HD patients [30,31,49,61]. However, approval of whether changes in collagen formation in HD are caused by external factors and metabolic changes or are influenced by genetic factors remains unsolved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, a reduction in the amount of connective tissue collagen was shown in HD. Other authors have reported a decrease in the ratio of type I to III collagen leading to the impaired mechanical stability of the perivascular tissue in HD patients [30,31,49,61]. However, approval of whether changes in collagen formation in HD are caused by external factors and metabolic changes or are influenced by genetic factors remains unsolved.…”
Section: Discussionmentioning
confidence: 99%
“…Van Gieson's and Picro Sirius red staining were used for the assessment of collagen. The sections stained in Picro Sirius red were further observed under interference and polarized light that improves the visualization and assessment of collagen fibers using a Biolar microscope (BIOLAR, Warsaw, Poland) [30,31,49]. The density of connective tissue fibers appearing in Van Gieson's and Picro Sirius red staining was graded semiquantitatively from 0 to 4, where: 0-loose, 1-minimally dense, 2moderately dense, 3-markedly dense, and 4-very dense.…”
Section: Histopathological and Histochemical Investigation Of Anorect...mentioning
confidence: 99%
See 1 more Smart Citation
“…A study has suggested that patients with hemorrhoids had a roughly two-fold greater chance of developing CRC and highlighted the urge to screen colonoscopy for patients with hemorrhoids ( 29 ). Furthermore, colonoscopy was recommended for patients with hemorrhoids because CRC and hemorrhoids share similar lifestyle-associated risk factors, including low fiber consumption, obesity, and insufficient exercise ( 39 ).…”
Section: Discussionmentioning
confidence: 99%